Recursos didáticos inovadores no processo de ensino-aprendizagem em história: revisão sistemática de literatura - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The focus of this article is on identifying innovative teaching resources that can be used to facilitate the teaching-learning process in History. In this sense, the work has the following objectives: To present didactic resources aimed at teaching History; To understand what skills can be developed through the pedagogical resources found; To know what element of innovation the didactic resource brings to history classes. The exploratory research was carried out through a Systematic Literature Review (SLR), using scientific articles found on Google Scholar and Capes Periodicals, from 2019 to 2024. The aim was to analyze articles that dealt with “Teaching Resources” and “History Teaching”. Eight papers were found that met the established categories. The study showed that innovation in the teaching-learning process is necessary, making an analysis of the school reality and the possibilities, modifying what already exists or bringing something new, whether or not it involves technologies, favoring classes and learning.
Keywords: História - Estudo e ensino; Tecnologia educacional; Inovações tecnológicas; Didática; Ensino - Meios auxiliares; Aprendizagem; Ensino – Metodologia; History - Study and teaching; Educational technology; CNPQ::CIENCIAS HUMANAS